KVN (Klub Vesslykh i Nakhodchivykh) . KVN (Klub Vesslykh i Nakhodchivykh) . KVN (Club of the Merry and Inventive) . КВН (Клуб Весёлых и Находчивых) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Team performances. Contributors: Masliakov, Aleksandr Vasil'evich (Anchor) Выступление команд. Создатели: Масляков, Александр Васильевич (Ведущий/Ведущая)